EFFECT OF MINERAL ELEMENTS ON POTATO PHOTOSYNTHETIC PRODUCTIVITY - Sultonova N. M. (International Journal of Innovations in Engineering Research and Technology, 2023)
In order to determine the effect of mineral elements on the growth and development, yield, crop quality of the Picasso variety, as well as performance indicators, studies were conducted to determine the optimal nutrient medium under the influence of various ratios of NPKZnMg in greenhouse conditions.